Impact of antiretroviral therapy in primary HIV infection on natural killer cell function and the association with viral rebound and HIV DNA following treatment interruption - Pace, Matthew; Ogbe, Ane; Hurst, Jacob; Robinson, Nicola; Meyerowitz, Jodi; Olejniczak, Natalia; Thornhill, John P.; Jones, Mathew; Waters, Anele; Lwanga, Julianne; Kuldanek, Kristen; Hall, Rebecca; et al. (Frontiers in Immunology, 2022)
Natural Killer (NK) cells play a key role in controlling HIV replication, with potential downstream impact on the size of the HIV reservoir and likelihood of viral rebound after antiretroviral therapy (ART) cessation. It is therefore important to understand how primary HIV infection (PHI) disrupts NK cell function, and how these functions are restored by early ART. We examined the impact of commencing ART during PHI on phenotypic and functional NK cell markers at treatment initiation (baseline), 3 months, 1 year, and 2 years in seven well-characterised participants in comparison to HIV seronegative volunteers. We then examined how those NK cell properties differentially impacted by ART related to time to viral rebound and HIV DNA levels in 44 individuals from the SPARTAC trial who stopped ART after 48 weeks treatment, started during PHI. NK cell markers that were significantly different between the seven people with HIV (PWH) treated for 2 years and HIV uninfected individuals included NKG2C levels in CD56dim NK cells, Tim-3 expression in CD56bright NK cells, IFN- expressed by CD56dim NK cells after IL-12/IL-18 stimulation and the fraction of Eomes-/T-bet+ in CD56dim and CD56bright NK cells. When exploring time to viral rebound after stopping ART among the 44 SPARTAC participants, no single NK phenotypic marker correlated with control. Higher levels of IL-12/IL-18 mediated NK cell degranulation at baseline were associated with longer times to viral rebound after treatment interruption (P=0.028). Additionally, we found higher fractions of CD56dim NK cells in individuals with lower levels of HIV DNA (P=0.048). NKG2A and NKp30 levels in CD56neg NK cells were higher in patients with lower HIV DNA levels (p=0.00174, r=-0.49 and p=0.03, r= -0.327, respectively) while CD27 levels were higher in those with higher levels of HIV DNA (p=0.026). These data show NK cell functions are heterogeneously impacted by HIV infection with a mixed picture of resolution on ART, and that while NK cells may affect HIV DNA levels and time to viral rebound, no single NK cell marker defined delayed viral rebound.